Atomic force microscopy (AFM) and 3D confocal microscopy as alternative techniques for the morphological characterization of anodic TiO2 nanoporous layers - Oyarzún Jerez, Diego Patricio (2016)
The morphologic characterization of self-organized TiO2 nanostructures by field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) was compared with results obtained by both atomic force microscopy (AFM) and 3D confocal microscopy, which were employed as alternative characterization methods. It is demonstrated that AFM with tuning fork configuration (intermittent mode) is also a powerful tool that allows obtaining conclusive information on the morphology of one-dimensional nanostructures. 3D confocal microscopy employed for the first time for obtaining thickness of nanoporous TiO2 films, is a new and powerful method that provides definite information on thickness of the nanostructures. The results employed for the characterization are fairly reliable besides novel and interesting.